A comparative study to know the effect of ropivacaine 0.5% and a mixture of bupivacaine 0.5% and lidocaine 2% on intraocular pressure following peribulbar block in cataract operation - Rekha Ramesh Mudhol; Lingamaneni Sneha (BLDE University Journal of Health Sciences, 2025)
PURPOSE: The purpose of this study was to evaluate the effectiveness of ropivacaine 0.5% and the combination of bupivacaine 0.5% and lidocaine 2% on intraocular pressure (IOP) before and after the peribulbar anesthesia in cataract operation and to know the ideal drug with minimal complications. METHODS: A double-blinded, randomized study was done on 62 patients with cataracts planned for cataract operation under regional anesthesia who were allotted to Group 1 and Group 2: 0.5% ropivacaine was given to Group 1 and 0.5% bupivacaine and 2% lidocaine mixture were given to Group 2. A detailed eye examination was done. Peribulbar block with 8 ml of the drug, given in the inferotemporal quadrant, and IOP was measured with a rebound tonometer (iCare IC100) preblock and postblock at 1, 5, and 15 min. Postblock akinesia, pain, surgical satisfaction, and motor recovery scorings were done. P value was deemed statistically significant if it was below 0.05. RESULTS: 63.32 ± 7.167 was the mean age of patients in Group 1 and 60.39 ± 9.807 in Group 2. The postblock increase in IOP was seen in both groups, with the ropivacaine group (Group 1) having a significantly lower rise than Group 2. However, IOP returned to normal at the end of 15 min in Group 1 and Group 2. Akinesia, surgical satisfaction, and motor recovery showed significant results, and none of the patients reported pain. CONCLUSION: Based on the study’s findings, we can say that low-concentrated ropivacaine is a viable substitute for the most often-used combination of lidocaine and bupivacaine for a peribulbar block during cataract operation. To demonstrate the advantage of this low-concentrated ropivacaine over the other most commonly used medications in the peribulbar block, more research with a larger sample size and 0.5% ropivacaine is needed.